Carriage of multi-drug resistant Gram-negative pathogenic bacteria by the house fly Musca domestica (Dhaka University Journal of Biological Sciences, 2017)
Fifteen house flies were used to isolate bacteria from external body surface and alimentary tract. A total of 50 isolates were obtained from the house flies, of which 25 (50%) were collected from the external body surface and 25 (50%) from alimentary gut. Fifteen isolates (30%) were obtained from Shamsunnahar Hall (SN) dining room, 22 (44%) from Dhaka Medical College Hospital (DMCH) and 13 (26%) from Rokeya Hall (RH) canteen. Six Gram-negative bacteria were isolated from the house flies namely, Escherichia coli (36%), Shigella spp. (22%), Salmonella spp. (18%), Pseudomonas spp. (10%), Klebsiella spp. (8%) and Enterobacter spp. (6%). E. coli was the highest in number in all three study areas which was 33% in SN Hall dining, 36% in DMCH, and 39% in RH canteen. E. coli was present in 32 and 40% of external body surface and gut samples, respectively. Bacterial susceptibility to antimicrobial agents showed that E. coli isolates were highly resistant (66-77.7%) to ampicillin, ciprofloxacilin and penicillin antibiotics. Salmonella isolates were sensitive to chloramphenicol but it was (55.5%) resistant to ampicillin, penicillin, tetracycline, gentamycin and imipenem antibiotics. In case of Shigella and Pseudomonas, 72.72 and 80% isolates were resistant to tetracycline and chloramphenicol, respectively. Among the Enterobacter spp. 66.66% were resistant to chloramphenicol, imipenem, vancomycin and tetracycline, while Klebsiella showed 100% resistant pattern to tetracycline in the study. It was observed that house flies carry several multidrug resistant Gram-negative bacteria in their body surface and alimentary tract and played a role in the transmission of serious diseases to human.Dhaka Univ. J. Biol. Sci. 26(1): 91-99, 2017 (January)